1989
DOI: 10.1111/j.1525-139x.1989.tb00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Chronic Renal Disease

Abstract: Summary Hypozincemia is common in patients with hronic renal insufficiency, and in patients with ESRD treated with peritoneal and hemodialysis. The causes of the decreased plasma zinc concentration in these patients are not completely understood, but poor nutritional zinc intake, diets associated with attempts to prevent the progression of renal failure, prescribed mineral supplements and medications, hypoalbuminemia, diminished gastrointestinal zinc absorption, increased urinary zinc excretion and redistribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Zinc in kidney disease has been reviewed by several investigators [3,4,5,6,7]. Abnormalities in zinc metabolism are well documented in CKD patients [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc in kidney disease has been reviewed by several investigators [3,4,5,6,7]. Abnormalities in zinc metabolism are well documented in CKD patients [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc in kidney disease has been reviewed by several investigators [3,4,5,6,7]. Abnormalities in zinc metabolism are well documented in CKD patients [3,4]. A systematic review of hemodialysis patients showed that the zinc level was lower in hemodialysis patients, compared with controls [5], and zinc deficiency was highly prevalent [7].…”
Section: Introductionmentioning
confidence: 99%
“…e-Textbooks are downloadable to laptop, tablet, or smartphone and include searching capability, personal highlighting, annotation, linking, and possible inclusion of audio/video or interactive media. An example of a new e-textbook in nephrology is the recently published Chronic Renal Disease, which is available in both print and as an e-textbook (56). The book has a companion website with downloadable figures either as PDFs or PowerPoint slides along with an interactive test bank (57).…”
Section: E-textbookmentioning
confidence: 99%
“…An example of a new e-textbook in nephrology is the recently published Chronic Renal Disease, which is available in both print and as an e-textbook (56). The book has a companion website with downloadable figures either as PDFs or PowerPoint slides along with an interactive test bank (57).…”
Section: E-textbookmentioning
confidence: 99%